Konsep Islam Wasathiyah Sebagai Wujud Islam Rahmatan lil ‘alamin: Peran Nu dan Muhammadiyah dalam Mewujudkan Islam Damai di Indonesia - Zainun Wafiqatun Niam (Institut Agama Islam Negeri Palopo, 2019)
The one of anxieties facing Muslims is about acts of violence in the name of Islam. Qur'an has mentioned that the Prophet was sent on earth as a mercy (rahmah) to the universe, and then the “rahmah” in question is to be implemented as such? Indonesia as a country with the largest Muslim population in the world is famous for Islam that is able to merge with the diversity of race, religion and culture. One of the things that influenced one of them is the existence of the largest Islamic organization in Indonesia NU and Muhammadiyah who always try to show Islam wasathiyah and rahmah. The existence of NU and Muahammadiyah is believed to be a great support to the peace of Indonesia with all its diversity. This paper is intended to further explore the concept of wasathiyah NU and Muhammadiyah in an effort to realize a peaceful Islam in Indonesia. The research method used is literature research using resources such as books, journal articles and mass media to analyze the concept of Islamic organization NU and Muhammadiyah. The results show that NU and Muhammadiyah carry the same concept to show the peaceful face of Islam that can unite with the differences. This is evidenced by the concept brought by each of both Islam Nusantara and Islam berkemajuan.